Pathogenesis, Clinical Manifestations and Management of Immune Checkpoint Inhibitors Toxicity. Issue 5 (September 2017) - Inno, Alessandro; Metro, Giulio; Bironzo, Paolo; Grimaldi, Antonio M.; Grego, Elisabetta; Di Nunno, Vincenzo; Picasso, Virginia; Massari, Francesco; Gori, Stefania
Immune checkpoint inhibitors have emerged as an effective treatment for several tumor types and their use in clinical practice is expected to further increase in the immediate future. Although these agents are well tolerated, they are associated with a peculiar spectrum of toxicity, which is immune mediated and may potentially affect every organ. However, immune-related adverse events are mostly reversible if promptly diagnosed and adequately treated. Therefore, it is crucial that medical oncologists know how to diagnose and treat immune-related adverse events. This review focuses on the pathogenesis, clinical manifestations and management of immune-related toxicity of anti-CTLA-4 and anti-PD-1 antibodies.